Problem-Based Learning for Critical Reflections on Skill-based Courses Using DEAL Model - R., Leena Sri; Vetriveeran, Divya (Journal of Engineering Education Transformations, 2025)
Higher education institutions focus on improving both soft skills and engineering proficiencies among students. The learning progress requires a systematic assessment to know the areas of improvement to meet global competitiveness. Self-reflections and critical reflections on knowledge, skill, and behavior are crucial for an industry-ready graduate. Our work deals with conceptualization, course design, and rubrics design to achieve critical reflections on the graduate outcomes of the students. We have designed the rubrics to assess the behavioral and engineering skills needed to solve complex engineering problems that can be solved better as a team for life-long learning and developing ethical interpersonal skills. Our assessment patterns also helped students achieve higher-order thinking skills through experiential learning.